AB0724 Cardio-pulmonary disease management in patients with systemic sclerosis: cardio-rheumatology clinic and patient care standardisation proposal. (12th June 2018) - Spinella, A.; Lumetti, F.; Mattioli, A.V.; Coppi, F.; Rosario, R.; Cocchiara, E.; Colaci, M.; Ferri, C.; Salvarani, C.; Giuggioli, D.
Abstract : Background: Systemic sclerosis (SSc) is a chronic connective tissue disease characterised by endothelial dysfunction, dysregulation of fibroblasts with excessive fibrosis of the skin and internal organs and autoimmune abnormalities. Cardio-pulmonary manifestations are common in SSc and their detection in the early stage of the disease as well as their careful follow-up are mandatory in order to counteract their impact on the overall disease outcome. Despite the need of establishing a proper methodology, literature provides few reports about this issue. Objectives: To evaluate the activity of our Cardio-Rheumatology Clinic in order to optimise diagnostic management of cardio-pulmonary disease in SSc patients. Methods: We retrospectively analysed data from 350 consecutive SSc patients referred to our University-based Rheumatology Centre and SSc Unit (F/M 308/42; lc/dcSSc 45/305; mean age 50.8±14.7 years; mean disease duration 10.9±7.0 years). All patients underwent general and cardio-pulmonary assessment, in particular they were evaluated in the Cardio-Rheumatology Clinic. The following parameters were considered: physical examination; past and current drugs; blood tests, in particular Erythrocyte sedimentation rate-ESR, C-reactive protein-CRP, CPK enzymes, troponin, NT-pro-BNP, d-dimer, serum autoantibodies, 25-OH-vitamin D; capillaroscopy; pulmonary function tests; high resolution scan of the lungs (HRCT); standard electrocardiogram (ECG) and 24 hour Holter ECG monitoring; Doppler echocardiography; cardiac stress test; coronary angiography and right heart catheterization (RHC); cardiac MRI and CT; vascular ultrasound (intima-media-thickness, carotid-femoral and brachial-ankle pulse-wave-velocity). The clinicians decided to perform these examinations according to clinical picture and current methodologies. Results: In the last 12 months we assessed 300 patients with 1st-level screening (cardio-rheumatologic evaluation, standard ECG, Doppler echocardiography, pulmonary function tests, thoracic imaging). Among 2nd-level, 30 procedures of 24 hour Holter ECG and 15 RHC tests were performed. Cardiac MRI, coronary CT angiography and vascular ultrasound were assessed, when requested, as 3rd-level examinations (30 procedures). After 1 year we observed a mean time of 10±5 days between request and clinical cardio-rheumatologic evaluation, 20±12 days to perform 1st-level screening, 25±15 days to execute the 2nd-level examinations. Figure-1 shows Cardio-Rheumatology algorithm for the management of SSc cardio-pulmonary disease. Conclusions: The activity of our Cardio-Rheumatology Clinic optimises the cardio-pulmonary SSc assessment, determining an early detection of these harmful complications with reduced waiting times which are critical issues. Screening algorithms are useful to stratify the risk and to establish the most appropriate diagnostic-therapeutic protocols, improving outcome of scleroderma patients. The development of a cardio-pulmonary risk score and the standardisation of a patient care approach, according to international quality indeces, could represent further tools to optimise SSc management. Disclosure of Interest: None declared